Free for all : fixing school food in America - Poppendieck, Janet, 1945- (California studies in food and culture, 2010)
"How did our children end up eating nachos, pizza, and Tater Tots for lunch? Taking us on an eye-opening journey into the nation's school kitchens, this superbly researched book is the first to provide a comprehensive assessment of school food in the United States. Janet Poppendieck explores the deep politics of food provision from multiple perspectives--history, policy, nutrition, environmental sustainability, taste, and more. How did we get into the absurd situation in which nutritionally regulated meals compete with fast food items and snack foods loaded with sugar, salt, and fat? What is the nutritional profile of the federal meals? How well are they reaching students who need them? Opening a window onto our culture as a whole, Poppendieck reveals the forces--the financial troubles of schools, the commercialization of childhood, the reliance on market models--that are determining how lunch is served. She concludes with a sweeping vision for change: fresh, healthy food for all children as a regular part of their school day."--The publisher.